Anterior knee pain and evidence of osteoarthritis of the patellofemoral joint should not be considered contraindications to mobile-bearing unicompartmental knee arthroplasty: a 15-year follow-up. (May 2017) - Hamilton, T. W.; Pandit, H. G.; Maurer, D. G.; Ostlere, S. J.; Jenkins, C.; Mellon, S. J.; Dodd, C. A. F.; Murray, D. W.
Abstract : Aims: It is not clear whether anterior knee pain and osteoarthritis (OA) of the patellofemoral joint (PFJ) are contraindications to medial unicompartmental knee arthroplasty (UKA). Our aim was to investigate the long-term outcome of a consecutive series of patients, some of whom had anterior knee pain and PFJ OA managed with UKA. Patients and Methods: We assessed the ten-year functional outcomes and 15-year implant survival of 805 knees (677 patients) following medial mobile-bearing UKA. The intra-operative status of the PFJ was documented and, with the exception of bone loss with grooving to the lateral side, neither the clinical or radiological state of the PFJ nor the presence of anterior knee pain were considered a contraindication. The impact of radiographic findings and anterior knee pain was studied in a subgroup of 100 knees (91 patients). Results: There was no relationship between functional outcomes, at a mean of ten years, or 15-year implant survival, and pre-operative anterior knee pain, or the presence or degree of cartilage loss documented intra-operatively at the medial patella or trochlea, or radiographic evidence of OA in the medial side of the PFJ. In 6% of cases there was full thickness cartilage loss on the lateral side of the patella. In these cases, the overall ten-year function and 15-year survival was similar to those without cartilage loss; however they had slightly more difficulty with descending stairs. Radiographic signs of OA seen in the lateral part of the PFJ were not associated with a definite compromise in functional outcome or implant survival. Conclusion: Severe damage to the lateral side of the PFJ with bone loss and grooving remains a contraindication to mobile-bearing UKA. Less severe damage to the lateral side of the PFJ and damage to the medial side, however severe, does not compromise the overall function or survival, so should not be considered to be a contraindication. However, if a patient does have full thickness cartilage loss on the lateral side of the PFJ they may have a slight compromise in their ability to descend stairs. Pre-operative anterior knee pain also does not compromise the functional outcome or survival and should not be considered to be a contraindication. Cite this article: Bone Joint J 2017;99-B:632–9